Netzhautkomplikationen bei Diabetes = Retinal complications in diabetes - Bertram, Bernd; Hammes, Hans-Peter (Der Diabetologe, 2016)
In September 2015 a revised version of the guideline “Prevention and therapy of diabetes-induced retinal complications” was released in Germany. It summarizes current recommendations for diagnosis and therapy of diabetic retinopathy with a special focus on practicability in daily routine. Newly included were the use of optical coherence tomography (OCT) for the diagnosis of diabetic macular edema and the evaluation of the therapeutic effect of anti-VEGF drugs (VEGF: vascular endothelial growth factor) or corticosteroids after intravitreal drug delivery. Screening intervals for diabetic retinopathy were extended to every 2 years for all diabetic patients with no retinopathy and limited systemic risk factors. Patients with known risk factors should be screened annually or in case of retinopathy, followed-up as recommended by the ophthalmologist.
Gesehen am 18.04.2019